Lightweight wrinkle synthesis for 3D facial modeling and animation. (January 2015) - Li, Jun; Xu, Weiwei; Cheng, Zhiquan; Xu, Kai; Klein, Reinhard
Abstract: We present a lightweight non-parametric method to generate wrinkles for 3D facial modeling and animation. The key lightweight feature of the method is that it can generate plausible wrinkles using a single low-cost Kinect camera and one high quality 3D face model with details as the example. Our method works in two stages: (1) offline personalized wrinkled blendshape construction. User-specific expressions are recorded using the RGB-Depth camera, and the wrinkles are generated through example-based synthesis of geometric details. (2) Online 3D facial performance capturing. These reconstructed expressions are used as blendshapes to capture facial animations in real-time. Experiments on a variety of facial performance videos show that our method can produce plausible results, approximating the wrinkles in an accurate way. Furthermore, our technique is low-cost and convenient for common users. Highlights: We present a lightweight non-parametric approach to generate wrinkles for 3D facial modeling and animation. Our method represents a convenient approach for generating plausible facial wrinkles with low-cost. Our method enables the reconstruction of captured expressions with wrinkles in real-time.